1,25-dihydroxyvitamin D as Predictor of Renal Worsening Function in Chronic Kidney Disease. Results From the PASCaL-1,25D Study - Galassi, Andrea; Fasulo, Eliana Maria; Ciceri, Paola; Casazza, Roberta; Bonelli, Fabrizio; Zierold, Claudia; Calleri, Mariella; Blocki, Frank A.; Palmieri, Maria Assunta; Mastronardo, Claudio; Cozzolino, Mario G. (Frontiers in Medicine, 2022)
Background. Heterogeneous progression of chronic kidney disease (CKD) toward dialysis advocates improving in renal care management. Diagnosis and staging of CKD relies on estimated glomerular filtration rate (eGFR) and albuminuria. Tubular biomarkers emerged as new predictors of worsening renal function (WRF), due to partial inaccuracy of eGFR and existing WRF in non-proteinuric patients. Active vitamin D is synthesized in renal tubules and participates to mineral adaptation in CKD. Circulating 1,25-dihydroxyvitamin D [1,25(OH)2D] was poorly investigated as a biomarker of endocrine tubular function and predictor of WRF. Objective. Investigate capability of 1,25(OH)2D to predict parathormone (PTH) increase and WRF in CKD stage 3-4. Methods. PASCaL-1,25D was an observational, prospective, monocentric study. Primary outcomes were absolute and 20% increase in PTH, and WRF defined as 20% reduction in eGFR or dialysis initiation at 6 months. Results. 71 patients completed follow up. Absolute increase in PTH (1-84) was independently predicted by lower 1,25(OH)2D levels (p= 0.0134). No association was detected between 1,25(OH)2D and iPTH increase. Higher 1,25(OH)2D was associated with reduced risk of WRF at univariate analysis [OR 0.89 (95% CI 0.86-0.93), p = 0.006]. The 1,25(OH)2D / PTH (1-84) ratio was associated with non-significant 84% risk reduction for WRF [OR 0.16 (95% CI 0.06 – 0.41), p = 0.05]. Low 1,25(OH)2D reached 100% sensitivity in predicting WRF in CKD stage 3 (AUC 9.909, p < 0.0001) and non-elderly patients (AUC 0.883, p < 0.0001). Machine learning models retained 1,25(OH)2D / PTH (1-84) as relevant predictor of WRF together with eGFR and albuminuria. Age influenced interaction between renal and mineral biomarkers. Conclusion. 1,25(OH)2D deserves attention as biomarker of tubular health, and sensible predictor of WRF on the short run among non-elderly patients affected by stage 3 CKD. The 1,25(OH)2D / PTH (1-84) ratio may represent a composite biomarker of tubular reserve / endocrine response to the transition from adaptive to maladaptive equilibrium in CKD-MBD.